Towards a better understanding of adaptation of local breeds to livestock farming systems : an exploratory methodological proposal - Paoli J.C.; Viollet A.; Santucci P.M.; Gambotti J.Y.; Lauvie A. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Local breeds are often described as adapted to local conditions, but we noticed a lack of characterization of what this adaptation refers to, in particular for breeders themselves. Moreover a single local breed can be involved in a diversity of livestock farming systems types and fodder systems. We proposed a specific research method, aiming to explore adaptation of Corsican sheep local breed to livestock farming systems. We consider that breeders are the first breed managers and as a consequence that the attempt to understand their own point of view on adaptation and their corresponding managing practices is of first importance. We present our method, based on semi structured interviews conducted through a sample of breeders chosen among types of farming systems made up thanks to a preliminary agrarian diagnosis. The analysis of the first results of this survey allows us to discuss this exploratory method proposal.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)